Penyuluhan Hukum Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Nomor 21 Tahun 2020 tentang Penanganan dan Penyelesaian Kasus Pertanahan Pada Kampung Nendali Distrik Sentani Timur Kabupaten Jayapura - Pelupessy, Eddy; Pondayar, Yustus; Tanati, Daniel; Palenewen, James Yoseph; Hetharia, Melkias; Asmarani, Nur; Pelupessy, Sella Petrix; Pelupessy, Berd Elkiopas; Angwarmasse, Lena Claudia; Selviana, Evi (Yayasan Daarul Huda Kruengmane, 2025)
This community service was carried out because land issues are problems that often cause prolonged disputes in the dynamics of Indonesian society. The government's serious efforts to minimize or reduce land disputes are evidenced by the existence of a land case handling function at the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency which then issued policies related to the handling of land cases up to the latest amendment through the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 21 of 2020 concerning the Handling and Settlement of Land Cases. The methods used were lectures and discussions. From the results of this community service, it can be stated that the community in Nendali Village has understood the process of handling land cases in relation to the cancellation of Land Title Certificates which can be done through judicial institutions and outside the courts that contain administrative and/or legal defects.